Transporte de oócitos bovinos em meio de maturação sem controle de atmosfera gasosa - Leivas, Fábio Gallas (2002)
Two experiments were designed to evaluate the effect of a simulated transport of oocytes to be used in bovine embryo production. Cumulus-oocytes complex -COCs - (n=1586) obtained from slaughterhouse ovaries were submitted to IVM in medium TCM+HEPES for differents periods. In experiment I (7 repetitions) IVM of oocytes in TCM-199 performed in incubator with 5% CO2 in air during 24h (Control Group, n=208) was compared with IVM in TCM+HEPES in a 39oC water bath during 6h followed by complementar IVM for 18h under the same conditions of Control Group. In experiment II (11 repetitions), oocytes were randomly distributed in four treatments. In the Control Group, oocytes (n=296) were matured for 24h in modified TCM-199 plus Bicarbonate, HEPES, rFSH-h, Estrus Cow Serum (ECS), and Piruvate at 39oC in incubator with 5% CO2 and saturated humidity. Oocytes exposed to a simulated transport remained for 6 (T6, n=286), 12 (T12, n=294) and 18h (T18, n=301) in maturation medium containing TCM + HEPES, in a 39oC water bath, with the same components used in the Control Group, except for bicarbonate. After completion of each transport period, oocytes were transferred to plates with maturation medium to reach 24h in incubator. In Experiments I and II, after maturation, oocytes were fertilized in FERT-TALP with heparin using spermatozoa (1 x 106/mL) sorted by Swim-Up. Thereafter, possible zygotes were cultured in SOF for 8 days. In Experiment I, cleavage and blastocyst rates in D7 and D9 were similar. In experiment II, embryonic development rates at D7 were similar for Control, T6 and T12 groups, with a reduction (P<0,05) observed for group T18 when compared with Control and T12 groups. At D9, there was a lower production of expanded plus hatched blastocysts in T18 (P<0,05), without difference in hatched rate. The average number of cells from hatched blastocysts was similar in Control (136), T6 (125,5) and T12 (126,8) groups. These results indicate the possibility of transporting bovine oocytes in maturation medium containing TCM + HEPES, with no controlled gaseous atmosphere environment, at 39oC, for up to 12h. This technique offers a practical and efficient alternative for the transport of bovine oocytes for IVP.